Türkiye Türkçesinde -ma Ekinin Yapım Eki Olarak İşlevleri / Functions of the Derivative Suffix -ma in Turkey Turkish - Bayraktar Erten, Nesrin (Journal of History Culture and Art Research, 2017)
Abstract Functions of the suffix -ma suffix can be classified under three groups in Turkey Turkish. This suffix produces adjectives that are related with root meanings like dönme dolap, sallama çay, gömme dolap, and adjectives like bodoslama atla, silme doldur etc. Besides these functions, it produces permanent nouns like gözleme, sarma, dolma, dondurma, kuzukapama, sürme, etc. This study investigates the suffix -ma as a derivational form and its functions have been classified. The study also evaluates the frequency with which it is used to coin permanent nouns and adjectives. Öz -ma ekinin Türkiye Türkçesinde işlevlerini başlıca üç grupta toplamak mümkündür. -ma eki ile bir yandan dönme dolap, sallama çay, gömme dolap gibi örneklerde eklendiği eylem tabanıyla ilişkili sıfatlar ve bodoslama atla, silme doldur gibi zarflar yapılırken, öte yandan da gözleme, sarma, dolma, dondurma, kuzukapama, sürme örneklerinde görüldüğü gibi kalıcı adlar yapılmıştır. Kalıcı adlar içinde yemek adları, oldukça önemli bir yer tutmaktadır. Bu çalışmada -ma eki, bir yapım eki olarak değerlendirilecek ve örnekler çerçevesinde tasnif edilerek kalıcı ad ve sıfat yapımında kullanıldığı yerlerdeki sıklık ele alınacaktır.